Problematic Issues of the Administrative and Legal Status of the Police in the Baltic States (Lithuania, Latvia, Estonia) - SHAPOVAL, Roman; BYTIAK, Iurii; KHRYSTYNCHENKO, Nadiia; SOLNTSEVA, Khrystyna (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
This research article aims to analyze the essence of the notion ‘administrative and legal status of police bodiesʼ. Materials and methods include analysis of the target and structural and organizational elements of the administrative and legal status for each country; consideration of comments and proposals made by representatives of the public and experts, as well as problematic issues of the administrative and legal status of the police of countries: Estonia, Latvia, and Lithuania. Results of the article are that the international community and the Council of Europe, based on the national experience of different countries, have developed a set of norms and recommendations in the field of crime prevention measures, the perception of which is an important condition for qualitative improvement of police service, implementing it in accordance with the principles of legality, humanism, respect for human rights and freedoms and the citizen. In the conclusion of the article, it should be noted that there is still room for improvement and harmonization of the administrative and legal status of police in the Baltic countries